A critical exploration of heritage language learners’ identities within Hellotalk - Teske, Kaitlyn; Vollmer Rivera, Alexis (Revista do GEL, 2018)
There is a need for critical, inclusive analyses that uncover the constraints that reinforce monolingual ideologies and reject the expression of multilingual and multicultural identities that are evident in eTandem applications (ORTEGA, 2017; VOLLMER RIVERA, 2017; VOLLMER RIVERA; TESKE, 2018). One population that may be affected by these constraints are Heritage Language Learners (HLL), who make up a diverse group of learners that have varying linguistic and cultural knowledge stemming from language and cultural exposure generally stemming from a more familial and community context (POTOWSKI, 2005). Drawing on identity theory (CUMMINS, 2001, 2009), this study investigates how HLL (N = 11) construct their identities within the constraints of the dichotomous eTandem learning environment HelloTalk by examining participant-reported reflections. Vis-á-vis content analysis (KRIPPENDORF, 1989) informed by Critical Applied Linguistics (PENNYCOOK, 2001) the results showed that although some features promote collaborative relations of power, in general the design of the application fosters coercive relations of power.